Analisis Pengaruh Peningkatan Kapasitas Jalan Ruas Aswatama - Kawah Sikidang terhadap Arus Lalu Lintas - Kasih, Shindya; Soedarsono, Soedarsono; Poedjiastuti, Hermin (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the effect of increasing the capacity of the Aswatama – Kawah Sikidang road section on traffic flow in the Dieng tourist area. The accidental sampling technique was used to select the research sample on observation data after the project, and data before the project was obtained from the Banjarnegara Regency Transportation Agency. Data analysis was carried out descriptively quantitatively to describe the condition of the Gangsiran Aswatama – Kawah Sikidang road section before and after the increase in road capacity and using inferential statistics for the effect of the increase in capacity on traffic flow in the tourist area. The results showed that increasing road capacity on the Aswatama – Kawah Sikidang section successfully increased the road capacity, as well as reduced the degree of saturation (DS) which showed a significant improvement in traffic performance. The Mann-Whitney U test confirmed a significant difference in vehicle volume before and after the project which indicated that traffic flow became smoother despite the risk of induced demand in the future